Entomopathogenic Fungi for Tick Control in Cattle Livestock From Mexico - Alonso-Díaz, Miguel Angel; Fernández-Salas, Agustín (Frontiers in Fungal Biology, 2021)
Ticks are one of the main economic threats to the cattle industry worldwide affecting productivity, health and welfare. The need for alternative methods to control tick populations is prompted by the high prevalence of multiresistant tick strains to the main chemical acaricides and their ecological consequences. Biological control using entomopathogenic fungi (EPF) is one of the most promising alternative options. The objective of this paper is to review the use of EPF as an alternative control method against cattle ticks in Mexico. Metarhizium anisopliae sensu lato (s.l.) and Beauveria bassiana s.l. are the most studied EPF for the biological control of ticks in the laboratory and in the field, mainly against Rhipicephalus microplus; however, evaluations against other important cattle ticks such as Amblyomma mixtum and R. annulatus, are needed. A transdisciplinary approach is required to incorporate different types of tools, such as genomics, transcriptomics and proteomics in order to better understand the pathogenicity/virulence mechanism in EPF against ticks. Laboratory tests have demonstrated the EPF efficacy to control susceptible and resistant/multiresistant tick populations; whereas, field tests have shown satisfactory control efficiency of M. anisopliae s.l. against different stages of R. microplus when applied both on pasture and on cattle. Epidemiological aspects of ticks and environmental factors are considered as components that influence the acaricidal behavior of the EPF. Finally, considering all these aspects, some recommendations are proposed for the use of EPF in integrated control schemes for livestock ticks.